SEC3A acts as an effector of RabE1b to regulate auxin transport in arabidopsis - Lixin Qiao; Jie Chu; Nan Wang; Xiaoyun Tan; Feng Liu; Yiqun Bao (PLoS ONE, 2026)
The establishment and architectural growth of terrestrial plants critically depend on polar auxin transport, a process primarily driven by the asymmetric distribution of PIN proteins within the plasma membrane. In Arabidopsis, the exocyst, an evolutionarily conserved octameric vesicle-tethering complex, orchestrates the recycling of PIN proteins, with subunits such as SEC6, SEC8, and EXO70A1 having established roles in this process. However, how the exocyst is mechanistically integrated into PIN recycling networks and the regulatory hierarchy remain unsolved. Here, SEC3A driven by pollen-specific ProLAT52 promoter was transformed into sec3a / + background, generating two independent pollen rescued ( PRsec3a ) mutant lines PRsec3a-1 and PRsec3a-2 , and enabling investigation of SEC3A function in sporophytic growth related to PIN protein dynamics. PRsec3a exhibited stunted primary root elongation, disrupted gravitropism, and reduced auxin accumulation. Notably, endocytic recycling of PIN1, PIN2, and BRI1 proteins from the Brefeldin A-induced compartments was compromised in PRsec3a . Furthermore, SEC3A was identified as an effector of the small GTPase RabE1b, defining a novel regulatory axis. Together, these findings advance the understanding of Exocyst-mediated membrane trafficking and its pleiotropic roles in plant development.